HQs digital e iniciação em geometria nos anos iniciais do ensino fundamental: uma proposta didática - Martins, Rose Mary Kern (2019)
This report is the result of a Master's research in the Postgraduate Program in Technologies, Communication and Education in the line Media in Education in the Media and Education and Communication line of the Federal University of Uberlândia -UFU-, Uberlândia, MG, which addresses the initiation in Geometry in the Years Initials of Elementary School, using the Comics in digital format and having the software HagáQuê. The theoretical foundation is supported by authors such as Nacarato; Passos (2003), Rama; Vergueiro (2009), Kenski (2012), Pischetola (2016) and others that dialogue with the research. The methodological approach is based on Qualitative, from the Bibliographic Research and Analysis of Similares. The research has as target audience teachers of the Initial Years of Elementary School, more specifically from the 1st to the 3rd year, since it was realized the importance of seeking other teaching and learning ways in initiating the geometric figures using Digital Technologies. For that, a product was elaborated, which is a Didactic Proposal approaching the Initiation in Geometry through the textual genre History in Comics in digital format, having as support the HagáQuê software and the computer in the computer room.